Letter (copy) : Spanish seamen - Tewson, Vincent
025a-0042-001 Secretary's. HVT/FC/567. 31st May, 1940. Mr. W.R Spence, Sachel Court, Alford, Nr. Cranleigh, SURREY. Dear Mr. Spence, SPANISH SEAMEN Referring to our talk yesterday I have now ascertained that Mr. Marchbank is agreeble to Wednesday morning next, June 5th at 11 o'clock for the proposed meeting in connection with the above. Mr. Marchbank is getting into touch with Mr. Oldennbroek of the International Transportworkers' Federation, and we can than have a talk about the general position. I am hoping you will have something definite to report as a result of your talk with the Ministry of Shipping. Yours sincerely, Assistant Secretary. 292/946/25a/42